(untitled) (Journal of Hama University, 2022)
The research aimed to clarify the role of preparing developed cost standards based on target costing in reducing costs of businesses entities in the modern business environment, based on the role played by the target cost in reducing costs and strengthening the competitive position of the entity, in addition to the important role of planning and control entrusted to cost standards in the decision-making process. The research focused on the importance of moving to build the developed cost standards based on target costing instead of the traditional cost standards that ignore market variables and the cost of competitors. To achieve this research objectives, it was applied to one of the Syrian pharmaceutical industry facilities, by determining the standard costs of a pharmaceutical product based on the current standards and then comparing it with the specified competitive cost based on the selling price in the market to reset the cost standards and give them a strategic dimension, in order to achieve the goal of the research. The research found a set of results, the most important ones are: the preparation of developed cost standards based on target costing leads to reduce costs in the modern business environment, and that the standard costing system based on the developed standards is integrated with the target costing in terms of goals and strategies, and they work together to confront the variables modern business environment.